2013
DOI: 10.5039/agraria.v8i3a2441
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho agronômico de genótipos de soja hortaliça cultivados no recôncavo Baiano

Abstract: RESUMOO objetivo deste trabalho foi avaliar os componentes de produção da planta e a produtividade de quatro genótipos de soja hortaliça cultivados no recôncavo Baiano. O experimento foi realizado no campo experimental do Centro de Ciências Agrárias, Ambientais e Biológicas da Universidade Federal do Recôncavo da Bahia. O delineamento experimental foi em blocos casualizados, com sete repetições. Foram avaliados quatro genótipos de soja hortaliça: JLM 17, BR 94, BRS 267 e BRS 258, anos agrícolas de 2010 e 2011.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…Soybean growth, development, and yield are significantly influenced by a variety and a sowing date (Muhammad et al, 2009;Shegro et al, 2010;Santos et al, 2013;Li et al, 2014;Matsuo et al, 2016;Bakal et al, 2017). In our studies, six edamame varieties were grown; however, one of them -'Aoshizuku' did not form pods, therefore, the crop was not harvested.…”
Section: Discussionmentioning
confidence: 78%
“…Soybean growth, development, and yield are significantly influenced by a variety and a sowing date (Muhammad et al, 2009;Shegro et al, 2010;Santos et al, 2013;Li et al, 2014;Matsuo et al, 2016;Bakal et al, 2017). In our studies, six edamame varieties were grown; however, one of them -'Aoshizuku' did not form pods, therefore, the crop was not harvested.…”
Section: Discussionmentioning
confidence: 78%
“…Santos et al (2013) encontraram baixos valores para o número de vagens por planta de soja-hortaliça, devido aos genótipos testados terem crescimento reduzido com menor altura de plantas. Mauad et al (2010) relataram que o aumento da densidade de semeadura diminuiu linearmente o número de vagens por planta.…”
Section: Resultsunclassified
“…The variation ranged from 48.62 (control) to 59.66 (foliar fertilization in V4) grains per plant. Santos et al (2013) evaluated a number of soybean genotypes and reported similar values, with means of 40-67 grains per plant. Cultivar BRS Favorita RR ® had the largest number of grains per pod (2.51), which was statistically different from BRS 213 (2.29) and BRSMG 790A (2.09).…”
Section: Growth Traits and Yieldmentioning
confidence: 89%